Low circulating PCSK9 levels in LPL homozygous children with chylomicronemia syndrome in a syrian refugee family in Lebanon - Ayoub, Carine; Azar, Yara; Maddah, Dina; Ghaleb, Youmna; Elbitar, Sandy; Abou-Khalil, Yara; Jambart, Selim; Varret, Mathilde; Boileau, Catherine; El Khoury, Petra; Abifadel, Marianne (Frontiers in Genetics, 2022)
Familial chylomicronemia syndrome is a rare autosomal recessive disorder of lipoprotein metabolism characterized by the presence of chylomicrons in fasting plasma and an important increase in plasma triglycerides (TG) levels that can exceed 22.58 mmol/l. The disease is associated with recurrent episodes of abdominal pain and pancreatitis, eruptive cutaneous xanthomatosis, lipemia retinalis, and hepatosplenomegaly. A consanguineous Syrian family who migrated to Lebanon was referred to our laboratory after perceiving familial chylomicronemia syndrome in two children. The LPL and PCSK9 genes were sequenced and plasma PCSK9 levels were measured. Sanger sequencing of the LPL gene revealed the presence of the p.(Val227Phe) pathogenic variant in exon 5 at the homozygous state in the two affected children, and at the heterozygous state in the other recruited family members. Interestingly, PCSK9 levels in homozygous carriers of the p.(Val227Phe) were ≈50% lower than those in heterozygous carriers of the variant (p-value=0.13) and ranged between the 5th and the 7.5th percentile of PCSK9 levels in a sample of Lebanese children of approximately the same age group. Moreover, this is the first reported case of individuals carrying simultaneously an LPL pathogenic variant and PCSK9 variants, the L10 and L11 leucine insertion, which can lower and raise LDL-C levels respectively. TG levels fluctuated concomitantly between the two children, were especially high following the migration from a country to another, and were reduced under a low-fat diet. This case is crucial to raise public awareness on the risks of consanguineous marriages to decrease the emergence of inherited autosomal recessive diseases. It also highlights the importance of the early diagnosis and management of these diseases to prevent serious complications, such as recurrent pancreatitis in the case of familial hyperchylomicronemia.